A new role for the Endothelin-1/Endothelin-A receptor signaling during early neural crest specification - Bonano, Marcela (2008)
The neural crest is induced at the border of the neural plate in a multistep process by signals emanated from the epidermis, neural plate and mesoderm. In this work we show for the first time the existence of a neural crest maintenance step which is dependent on signals released from the mesoderm. We identified Endothelin-1 (Edn1) and its receptor (Ednra) as key players of this signal and we show that Edn1/Ednra signaling is required for maintenance of the neural crest by a dual mechanism of cell specification and cell survival. We show that: (i) Ednra is expressed in prospective neural crest; (ii) loss-of-function experiments with antisense morpholino or with specific chemical inhibitor suppress the expression of early neural crest markers; (iii) gain-of-function experiments expand the neural crest territory; (iv) epistatic experiments show that Ednra/Edn1 is downstream of the early neural crest gene Msx1 and upstream of the late genes Sox9 and Sox10; and (v) Edn1/Ednra signaling inhibits apoptosis and controls cell specification of the neural crest. Together, our results provide insight on a new role of Edn1/Ednra cell signaling pathway during early neural crest development.